2009
DOI: 10.2741/3466
|View full text |Cite
|
Sign up to set email alerts
|

MLL histone methylases in gene expression, hormone signaling and cell cycle

Abstract: Histone methyl-transferases (HMTs) are key enzymes that post-translationally methylate nuclear histone proteins and play critical roles in gene expression, epigenetic regulation and diseases in eukaryotic organisms. Mixed lineage leukemias (MLLs) are human HMTs that specifically methylate histone H3 at lyisine-4 and regulate gene activation. MLLs are also well known to be rearranged often in acute myeloid and lymphoid leukemias. Human encodes several MLLs that have similar enzymatic activities but diverse func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 86 publications
2
49
0
Order By: Relevance
“…Not all genes conclusively point to a male predisposition for developing ALL, in fact we found a female-specific-positive correlation of MllT6. Mixed lineage leukemias are histone methyl-transferases that regulate gene activation and are also well known to be rearranged in acute myeloid and lymphoid leukemias (48). Interestingly, the female-specific correlation might be in line with the literature.…”
Section: Era Caluxsupporting
confidence: 76%
See 1 more Smart Citation
“…Not all genes conclusively point to a male predisposition for developing ALL, in fact we found a female-specific-positive correlation of MllT6. Mixed lineage leukemias are histone methyl-transferases that regulate gene activation and are also well known to be rearranged in acute myeloid and lymphoid leukemias (48). Interestingly, the female-specific correlation might be in line with the literature.…”
Section: Era Caluxsupporting
confidence: 76%
“…Concordantly, differentially correlating leukemia and lymphoma genes with AR receptor activation do not conclusively support a male predisposition. In fact, next to the MLLT6 gene correlating with the ERa receptor, a female-specific positive correlation of MllT3 with AR receptor activation was found which might be related to female predisposition to develop infant leukemia (37,48,49).…”
Section: Ar Caluxmentioning
confidence: 99%
“…Notably, MLLs are well-known human histone H3K4-specific methyl-transferases that play key roles in gene activation (51, 71). There are several MLLs: MLL1, MLL2, MLL3, MLL4 and MLL5 (51, 71).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, MLLs are well-known human histone H3K4-specific methyl-transferases that play key roles in gene activation (51, 71). There are several MLLs: MLL1, MLL2, MLL3, MLL4 and MLL5 (51, 71). Recent studies from our (and others) laboratory demonstrated that MLLs (MLL1–4) acts as ER-coregulators and associated with ER-mediated gene activation (14, 15, 45, 49, 63, 69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation